GEOGRAPHIC VARIATION IN SELECTED LIFE HISTORY TRAITS OF THE EASTERN NARROWMOUTH TOAD, GASTROPHRYNE CAROLINENSIS (HOLBROOK, 1836), ALONG THE NORTHEASTERN EDGE OF ITS GEOGRAPHIC RANGE - Meshaka, Jr., Walter E.; Delis, Pablo R.; Walters, Katie (Journal of North American Herpetology, 2015)
We examined the Eastern Narrowmouth Toad,Gastrophryne carolinensis, along the northeastern edge of its geographic range in Virginia to determine the extent to which selected life history traits in this region adhered to patterns associated with a latitudinal gradient in this species. As in studies elsewhere, a significant difference in mean adult body size between males (28.3 mm SVL) and females (30.1 mm SVL) was typical of this species as was the absence of a relationship between clutch size and female body size. Mean body sizes of both sexes appeared larger in northern populations than southern counterparts. Geographically predictable, the breeding season in Virginia was severely curtailed in response to climatic constraints despite extended fertility, and its breeding activity peaked in mid-summer as it has been reported to do throughout its geographic range. Thus, along the northern edge of its geographic range, the Eastern Narrowmouth Toad retains its ability breed for a longer season despite present climatic constraints, an advantage in the face of climate change that could alter timing and duration of acceptable breeding atmospheric conditions.